2020
DOI: 10.1039/c9cp06779e
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the interfacial nanostructure of a deep eutectic solvent at a solid electrode

Abstract: The structure of an ionic liquid at an electrode interface was studied by a combination of neutron reflectometry measurements and molecular dynamics simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Hydrophobic deep eutectic solvents (DESs) have emerged as candidates that can extract organic substrates from aqueous environments. [1][2][3][4][5][6] The hydrophobic DESs are composed of organic hydrogen bonding donors and acceptors. Their extractive capabilities have been illustrated in pharmaceuticals, [6][7][8] food industry, 9 metal industry 10,11 and carbon dioxide capture applications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrophobic deep eutectic solvents (DESs) have emerged as candidates that can extract organic substrates from aqueous environments. [1][2][3][4][5][6] The hydrophobic DESs are composed of organic hydrogen bonding donors and acceptors. Their extractive capabilities have been illustrated in pharmaceuticals, [6][7][8] food industry, 9 metal industry 10,11 and carbon dioxide capture applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the DES-aqueous liquid-liquid interface may present a non-zero dipole moment since the molecules are likely to show a preferential orientation at the interface. 5,24,25 32 showed that the good water stability of the hydrophobic DESs is critical for their extraction ability. Kaul et al 33 studied the partitioning of n-alkanols and benzene derivatives in hydrophobic DES and water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, MD simulations provide atomic resolution unavailable to the experiments presented here. Combining MD simulations and scattering experiments is beneficial for studying phospholipid membranes but can also be used for the structural analysis of completely unrelated systems [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MD method is here the instrument of choice. As shown elsewhere, although one needs to take care of several practical details [ 22 , 35 , 38 , 39 ], it is relatively straightforward to compute the scattering pattern corresponding to an MD simulated structure and compare it to the experimental data. This goes beyond the normal fitting procedure in which a set of parameters describing the structure is optimized in order to reproduce the data.…”
Section: Introductionmentioning
confidence: 99%